If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8a + -6b + -3) + -1(-2a + 4b + 7) = 0 Reorder the terms: (-3 + 8a + -6b) + -1(-2a + 4b + 7) = 0 Remove parenthesis around (-3 + 8a + -6b) -3 + 8a + -6b + -1(-2a + 4b + 7) = 0 Reorder the terms: -3 + 8a + -6b + -1(7 + -2a + 4b) = 0 -3 + 8a + -6b + (7 * -1 + -2a * -1 + 4b * -1) = 0 -3 + 8a + -6b + (-7 + 2a + -4b) = 0 Reorder the terms: -3 + -7 + 8a + 2a + -6b + -4b = 0 Combine like terms: -3 + -7 = -10 -10 + 8a + 2a + -6b + -4b = 0 Combine like terms: 8a + 2a = 10a -10 + 10a + -6b + -4b = 0 Combine like terms: -6b + -4b = -10b -10 + 10a + -10b = 0 Solving -10 + 10a + -10b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10a + 10 + -10b = 0 + 10 Reorder the terms: -10 + 10 + 10a + -10b = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 10a + -10b = 0 + 10 10a + -10b = 0 + 10 Combine like terms: 0 + 10 = 10 10a + -10b = 10 Add '10b' to each side of the equation. 10a + -10b + 10b = 10 + 10b Combine like terms: -10b + 10b = 0 10a + 0 = 10 + 10b 10a = 10 + 10b Divide each side by '10'. a = 1 + b Simplifying a = 1 + b
| 9.1/1.4=c | | S+4s-s-1=19 | | 8x+6-9x=6(m+1) | | -21=7v+7(v+3) | | 5x+3-5x=-7 | | x-4/3=15 | | X/15=8/3 | | 7-1/3(9m-12) | | 48w=208 | | bc^5*b= | | u+(-7.5)=-12.2 | | 24x+15=7(3x+2)+3x+1 | | (12x+3y)-(6x+2y-4)= | | 7+6-3(1/2(6)) | | x/10+9=10 | | 11x-5=7x-53 | | 2.1x-43.1=8.4-3.2 | | 2.06+18=-10.84 | | 2(7-2)-5(7)=5(2-7) | | 4-2n=28 | | 3(2+-6)=3+-9 | | (x-7)/5=-7 | | 12y=11(y+19) | | N-2=5+2n | | -2.06d+2.7=-8.6 | | 8(6-9)=9(2(6)-12)-4(6) | | 7+6-3(1/2x6) | | 4/5=-4/7*g | | -3/3=15 | | 4(-x+2)=-8(-2x-4)+16 | | -(3p-2n-t)= | | -2/7n=-28 |